WAQF AND LEGACY OF ALTRUISM IN SINGAPORE: CHALLENGES AND DEVELOPMENT - Listiana, Lisa; Alhabshi, Syed Musa (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2020)
The success story of waqf development in Singapore has been significantly acknowledged. The successful experience warrants for learning models for comparative experiences among other Muslim countries in Asia. This study document and analyze to share two main research objectives related to the Waqf practices. First, it aims to explore and elaborate on the dynamics of waqf administration and property development in Singapore. Second, analyzes the significance of past altruistic waqf landmark activities towards the Muslim community in Singapore. Based on prior studies, this research phenomenon has yet to be addressed and highlighted in any previous study. A qualitative approach with a case study research design is applied in this research. In-depth semi-structured interview sessions with 4 private mutawallis are complemented with reviews of relevant documents. This study finds that external factors, including mandatory acquisition by the government, higher living costs, and several legal restrictions represent the main challenges to the waqf sector in the country. On other hand, effective governing roles played by MUIS as waqf authority in the country enable the initiative of new waqf type and redevelopment of existing waqf properties. In the present time, these endowed properties provide benefits not only for the Muslim community in Singapore but also to significant other beneficiaries outside Singapore. The findings of this study indicate that the legacy of waqf inspires altruism in the modern Singaporean Muslim community. It becomes the basis for contemporary waqf practice among Muslims in Singapore and assists them to be a self-sustaining passionate and harmonic community.Keywords: Altruism, Legacy, Muslim Community, Singapore, Waqf